Aboriginal Land Rights and the Mining Industry in the Northern Territory (The Australasian Institute of Mining and Metallurgy, 1984)
The impact of moves to introduce Abori- ginal land rights was felt in the Northern Territory as early as 1972 when the Federal Government froze the processing of all appli- cations for mining interests over vacant Crown land. The Aboriginal Land Rights (Northern Territory) Act was finally proclaimed on Aust- ralia Day 1977 and since that date the mining industry and the Territory legislature have struggled to make the Act work. Despite these efforts long delays have been experienced by those required to negotiate mining and explor- ation agreements under the Act. In fact explor- ation on Aboriginal land has been effectively stiffled since the introduction of the Abori- ginal Land Rights Act. The Northern Territory government and the mining industry have both sought amendment to the Act to remedy some of its more onerous problems. These efforts have generally been fruitless. Some of the recommendations put forward by Mr Justice Toohey following his recent review of the Act would provide relief in some important areas. However, any such improvements are more than offset by a number of Mr Justice Toohey's recommendations which would severely disadvantage the vast majority of Territorians. A recent survey of mining companies seeking exploration licences over Aboriginal land indicates that many of the existing diffi- culties could be overcome without significant amendment to the Act but rather by the adoption of a positive administrative approach by the Land Councils. It is now up to the Commonwealth and the Land Councils to demonstrate that their Act can work without crippling the Northern Territory economy and its mining industry.